Suggestions on Writing for Publication in Language Learning Journals - George M. Jacobs (TEFLIN, 1999)
This article provides suggestions on writing for journals in the field of language learning. These suggestions are presented in three sections. The first section discusses how to begin. Suggestions in this section are that we appreciate the benefits of writing for publication, develop good ideas, work efficiently, ponder options as to what type of writing to do, choose a good topic, consider replication of others research, and cooperate with others. The second section presents suggestions on doing the actual writing. Here, it is suggested that we connect ideas, delve deeply into the ideas we present, strive to write the reader friendly manner, use visuals, and improve our writing by noticing how other journal authors write. The third section concerns relations with editors. The advice given is that we choose carefully the journal to which we submit our work, follow that journals directions to contributors, include a cover letter, be prepared to wait patiently, welcome critical feedback from editors and reviewers, and view editors as colleagues.